1983
DOI: 10.1161/01.cir.67.6.1178
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of coronary vasoconstriction by beta-adrenergic blockade in patients with coronary artery disease.

Abstract: SUMMARY Although ,t-adrenergic blocking agents reduce myocardial oxygen consumption and symptoms of myocardial ischemia in patients with coronary artery disease (CAD), propranolol has been reported to exacerbate coronary artery spasm in some patients with variant angina. To determine whether increased coronary vasomotor tone can be induced by 3-adrenergic blockade, we measured the changes in coronary vascular resistance (CVR) during cold pressor testing (CPT) in 15 patients, nine with severe CAD and six with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(42 citation statements)
references
References 48 publications
(13 reference statements)
1
40
1
Order By: Relevance
“…Previous data from Kern et al 22,23 have suggested that ␤-blockers (intravenous propranolol) could potentiate coronary vasoconstriction in patients with coronary artery disease undergoing a cold pressor test because of an unopposed ␣-adrenergic vasomotor tone. On the contrary, Gaglione et al 24 showed a significant vasodilation of stenotic coronary arteries after intracoronary propranolol in patients undergoing supine bicycle stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from Kern et al 22,23 have suggested that ␤-blockers (intravenous propranolol) could potentiate coronary vasoconstriction in patients with coronary artery disease undergoing a cold pressor test because of an unopposed ␣-adrenergic vasomotor tone. On the contrary, Gaglione et al 24 showed a significant vasodilation of stenotic coronary arteries after intracoronary propranolol in patients undergoing supine bicycle stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…17,29 Previous studies have already documented that ␤-adrenergic blockade can potentiate coronary artery constriction in patients with coronary artery disease, which is most likely mediated by unopposed ␣-adrenergic vasomotor tone. 33 In addition, it has been shown that adrenergically mediated coronary vascular tone may contribute to ischemia in patients with coronary disease. 34 Responses of coronary arterioles and small arteries to NE have been investigated by many studies in vivo and in vitro, revealing that adrenoceptors are located on several cell types and tissues, including endothelium, 4,17-28 smooth muscle, 26 -28 …”
Section: Discussionmentioning
confidence: 99%
“…There is the concern that β-blockers would impede β-adrenergic mediated vasodilation.There have been reports of β-blocker associated decrease in coronary blood flow, increased seizure activity, and possible increased mortality. 36,37 However, β-blockade may be beneficial against the pathophysiologic effects of cocaine in the peri-MI period, including systolic dysfunction heart failure, coronary artery thrombotic occlusion, and ventricular arrhythmias. A recent retrospective cohort study concluded that the administration of β-blockers after the acute event was associated with a reduction in the incidence of MI after cocaine use and that the benefit of β-blockers on myocardial function may offset the risk of coronary artery vasospasm.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%